Komunikasi Crosshijaber di Kota Bandung - As, Enjang; Aliyudin, Mukhlis; Rohman, Ujang (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2021)
This study aims to determine the motives of the goals and causes of Crosshijaber Communication Behavior in the city of Bandung. This study uses a phenomenological method with a qualitative approach. The process of collecting data was obtained through in-depth interviews and observations of informants. The results showed that the motives that caused Crosshijaber's Communication Behavior were, among others, because of problems within themselves and their families, thus creating a sense of trauma to the perpetrators. They feel bored with their original appearance and make them do something new. Interest in hijab makes them want to try using it, while the motives for Crosshijaber Communication Behavior are, among others, feeling suitable when they use the hijab after they wear the hijab the Crosshijaber actors will get happiness, their goal of using the hijab is to want to be a better person, to satisfy their sense of belonging. I'm curious why women using hijab become more beautiful.